1986
DOI: 10.1254/jjp.41.173
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Inhibitory Action of Phenylephrine in Guinea-Pig Taenia Coli

Abstract: Abstract-The effect of phenylephrine, an a-agonist, on the Ca movements and the influence of removal of external Na+ on the relaxant activity of phenylephrine were examined in the taenia coil of guinea pigs. Phenylephrine (10-7-10-5 M) caused dose-dependent relaxation of the taenia coli contracted by 20 mM KCI in Locke-Ringer solution. Phenylephrine (10-5 M) suppressed the spike discharges of the taenia coil evoked by 20 mM KCI without affecting the membrane potential, and this was accompanied by the muscle re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1988
1988
1988
1988

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…It has been shown that a high concen tration of KCI induces sustained contraction of smooth muscle in the absence of external Na+ (7,8). In the present study, we explored the effects of Na+-free, sucrose or Tris …”
mentioning
confidence: 95%
“…It has been shown that a high concen tration of KCI induces sustained contraction of smooth muscle in the absence of external Na+ (7,8). In the present study, we explored the effects of Na+-free, sucrose or Tris …”
mentioning
confidence: 95%